Research progress on high-efficiency lubrication and cooling technology for aircraft engine main spindle bearings - LIU Zhenxia; ZHU Zetao; JIANG Le; LYU Yaguo; QIN Jingwen (Hangkong gongcheng jinzhan)
Rolling bearings are the critical components of aircraft engines，which require the efficient lubrication and cooling technologies to ensure stable operation under the harsh conditions of high speed，high temperature，and heavy load. Compared to traditional jet lubrication，the under-race lubrication because of numerous advantages has become the mainstream lubrication method for modern engine main shaft bearings. According to the efficient lubrication and cooling technology for aircraft engine main shaft bearings，the typical lubrication methods are compared. The current development status of under-race lubrication technology is systematically reviewed and summarized， and the lubrication and cooling effects of under-race lubricated bearings are discussed. The future development trends in lubrication and cooling technology for high-speed bearings in aircraft engines are explored，which can provide the reference for efficient lubrication，cooling，and refined thermal management of aviation bearings.